Revisiting Practical Wisdom: A Reinterpretation of Ḥikmah Muta‘āliyah in Political Thought - Muhammad Rahim (Politeia: Jurnal Ilmu Politik, 2026)
Philosophy is often reduced to a static enterprise of systematizing inherited traditions, losing its fundamental role in re-interpreting reality. In the context of Islamic thought, Ḥikmah Muta‘āliyah—despite its core principle of "becoming" (ṣayrūrah)—frequently faces stagnation due to museological approaches. There is an urgent need to bridge the gap between this classical metaphysical tradition and contemporary political challenges. This study aims to provide a renewed interpretation of Ḥikmah Muta‘āliyah by rethinking its practical wisdom (ḥikmah ʿamalī) to establish a dynamic framework for political rationality. It seeks to demonstrate how this tradition can serve as a living horizon for political insight. The research employs a combination of critical philosophical hermeneutics and reconstructive analysis. The methodological framework unfolds through conceptual retrieval, critical rearticulation, and the development of orienting principles for modern political judgment. The study reveals that Ḥikmah Muta‘āliyah functions as a robust framework that naturally accommodates methodological pluralism. By its integrative nature, it synthesizes intuitive, rational, and empirical modes of inquiry, providing a platform for interdisciplinary studies where metaphysics, ethics, and social sciences converge. This approach allows for a "scientific" political analysis that is neither dogmatic nor detached from historical reality. Rereading Ḥikmah Muta‘āliyah enables the development of an emergent political foundation. It concludes that this tradition’s greatest strength lies in its ability to foster a "fusion of horizons," acting as an interdisciplinary bridge that invites diverse methodological perspectives to address complex contemporary political issues. Keyword: Islamic Philosophy, Ḥikmah Muta‘āliyah, Practical Wisdom, Methodological Pluralism, Interdisciplinary Studies.